The knee joint extensor and flexor strength indicators in judo female athletes - Witkowski, K.; Piepiora, P.; Grochola, M. (Archives of Budo Science of Martial Arts and Extreme Sports, 2018)
Background & Study Aim: Muscle strength, namely the capacity for overcoming the external resistance or counteracting it at the expense of muscular effort, plays an unquestionably essential role in judo competitor's training. The objective of this study has been knowledge about the values of torques, torque gradient and muscle strength deficit released by knee joint extensors and flexors at rest by judo female competitors, taking up specialist strength training.